NILAI MORAL DAN SIKAP TOKOH TERHADAP KEHIDUPAN MASYARAKAT DALAM NOVEL GADIS KRETEK KARYA RATIH KUMALA - Kencana, Diya (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Moral Values and Attitudes of Leaders Against the Life of Society in Novel by Ratih Kumala. What are the moral values and attitudes of the characters towards people's lives in the novel Kretek Girl by Ratih Kumala. This study aims to describe the moral values and attitudes of the characters in the novel Kretek Girl by Ratih Kumala. The method used is a qualitative descriptive method, which is a method by systematically describing the facts and characteristics of objects and subjects that are precisely examined. Data collection techniques used are documentation techniques, namely data collection techniques by finding and collecting data on matters in the form of data, transcripts, books, newspapers, magazines, minutes, report cards, agendas and so on. The main document used in this study is the novel Kretek Girl by Ratih Kumala. Based on the results of the study, it can be concluded that moral values and attitudes towards people's lives can be taken in Ratih Kumala's novel Kretek Girl, that we must strive to achieve success in living life, not depend on others, respect and respect each other, we must be devoted to parents, and we must maintain the trust of others, not to divulge the secrets of others.